Sand Brick Using Perlite as a Cement Replacement - Azeman Shah, Muhammad Asyraf; Adnan, Suraya Hani; Osman, Mohamad Hairi; Ahmad Jeni, Mohamad Luthfi; Jamellodin, Zalipah; Abdul Hamid, Noor Azlina (Progress in Engineering Application and Technology, 2020)
Brick is a group or masonry or building material used for the construction of a building structure as a partition wall for a building or as a brick fence. At that time, almost no uses of perlite in the construction industry made perlite very uncommon. Perlite is commonly used in the agriculture or crop industry because of it has moisture content properties. The perlite material contains characteristics of light weight in the lightweight aggregate class. In this study, 0%, 1%, 3% and 5% of perlite material is used in sand brick mixing. In addition, three samples per test were performed to determine the optimal percentage. A total of 2 laboratory tests will be carried out to achieve the planned objectives such as brick density and water absorption test.